2016
DOI: 10.1007/s10815-015-0633-9
|View full text |Cite
|
Sign up to set email alerts
|

A combination of hydroxypropyl cellulose and trehalose as supplementation for vitrification of human oocytes: a retrospective cohort study

Abstract: Our data demonstrate that HPC and trehalose are suitable and safe substitutes for serum and sucrose. Therefore, the new commercial media can be used efficiently in the vitrification of human oocytes avoiding viral and endotoxin contamination risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 50 publications
1
30
0
Order By: Relevance
“…It is, however, worth noting that serum contains a wide variety of elements, including hormones, growth factors, vitamins, peptides and many other unknown molecules that stimulate cell division (Coello et al., ; Men, Agca, Critser, & Critser, ). Serum acts as a scavenger of embryotoxic components and protects cell membranes during freezing process (Coello et al., ). Amorim et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is, however, worth noting that serum contains a wide variety of elements, including hormones, growth factors, vitamins, peptides and many other unknown molecules that stimulate cell division (Coello et al., ; Men, Agca, Critser, & Critser, ). Serum acts as a scavenger of embryotoxic components and protects cell membranes during freezing process (Coello et al., ). Amorim et al.…”
Section: Discussionmentioning
confidence: 99%
“…In the 1980s, human serum was considered as the common albumin source; since then, the whole serum was replaced by albumin sources. Recently, human serum albumin (HSA) has been widely used as an embryo culture supplement to improve clinical outcome (Adler, Reing, Bedford, Alikani, & Cohen, ; Coello, Campos, Remohí, Meseguer, & Cobo, ; Menezo, Testart, & Perrone, ; Pool & Martin, ).…”
Section: Introductionmentioning
confidence: 99%
“…Desirable advantages that are sought in HPC-supplemented, protein-free solutions are reduced production cost and variability, and eliminating the hypothetical risk of viral contamination associated with protein purified from blood [24]. The addition of hydroxypropyl cellulose instead of serum to vitrification solutions can provide the same viscosity that enables in vitro manipulation and enhances the glass-forming tendency of the solution, without the aforementioned drawbacks [25,28].…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary studies have shown promising results of HPC supplementation of vitrification solutions on murine oocytes and blastocysts in terms of survival and embryo development [26,27]. Recently, direct comparative studies revealed the similarity of HPC and SSS-based formulations for human oocytes vitrification [25,28].…”
Section: Introductionmentioning
confidence: 99%
“…However, the highest vitrification efficiency for immature horse oocytes was reached when a vitrification medium containing trehalose was used (42% maturation (10/24), 80% cleavage (8/10) and 10% blastocysts (1/10)), whereas no blastocysts were obtained from sucrose-containing media (Canesin et al 2017). In humans and mice, oocyte vitrification in trehalose-containing medium is also associated with higher blastocyst rates than vitrification with sucrose (Coello et al 2016), but the difference is not always statistically significant Lestari et al 2018), probably due to variations in the protocols used. Injection of sugars into the oocyte can avoid osmotic stress associated with the use of non-permeating CPAs (Woelders et al 2018).…”
Section: Equilibration Solutionmentioning
confidence: 99%